2013
DOI: 10.1186/1472-6882-13-215
|View full text |Cite
|
Sign up to set email alerts
|

Pilot randomized trial on mindfulness training for smokers in young adult binge drinkers

Abstract: BackgroundWe report results of a pilot study designed to test a novel smoking cessation intervention, Mindfulness Training for Smokers (MTS), in smokers age 18-29 years with regular episodes of binge drinking. Mindfulness is a cognitive skill of applying close moment-to-moment attention to experience with a mental posture of acceptance and non-reactivity. The MTS intervention consisted of six weekly classes that provided instruction on how to use mindfulness to manage known precursors of smoking relapse includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 62 publications
(77 reference statements)
0
46
0
1
Order By: Relevance
“…Only two of the studies reported comorbid medical conditions or special populations. One of these was a study of young binge drinkers (Davis, Mills, et al, 2013). In the other study, the participants had mild intellectual disability .…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only two of the studies reported comorbid medical conditions or special populations. One of these was a study of young binge drinkers (Davis, Mills, et al, 2013). In the other study, the participants had mild intellectual disability .…”
Section: Participantsmentioning
confidence: 99%
“…The mindfulness intervention was delivered remotely, via personal digital assistant, in one of the studies (Ruscio et al, 2015). Four of the studies delivered the mindfulness intervention in an outpatient setting (Davis, Mills, et al, 2013;Davis, Goldberg, et al, 2014a;Davis, Manley, et al, 2014b;Tang, Tang, and Posner, 2013). In four of the studies, it was unclear where the intervention was delivered (Bowen and Marlatt, 2009;Brewer et al, 2011;Rogojanski, Vettese, and Antony, 2011a;Singh et al, 2014).…”
Section: Settingmentioning
confidence: 99%
See 3 more Smart Citations